2020
DOI: 10.2147/copd.s231004
|View full text |Cite
|
Sign up to set email alerts
|

<p>Triple Therapy with Budesonide/Glycopyrrolate/Formoterol Fumarate Improves Inspiratory Capacity in Patients with Asthma-Chronic Obstructive Pulmonary Disease Overlap</p>

Abstract: Purpose: Asthma-chronic obstructive pulmonary disease overlap (ACO), characterized by airway limitation, is an important condition with high incidence and mortality. Although some guidelines recommend triple therapy with inhaled corticosteroids/long-acting muscarinic antagonists/long-acting β 2 agonists, this treatment approach is based on the extrapolation of data from studies of asthma or chronic obstructive pulmonary disease (COPD) alone. Methods: A 12-week, randomized, open-label cross-over pilot study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
(78 reference statements)
0
9
1
1
Order By: Relevance
“…Another clinical trial is assessing the therapeutic potential of an oxyhydrogen generator delivered by nebulizer to COPD patients (NCT02850185). The combination of LAMA with LABA therapies has proven effective in COPD treatment, several studies showed their efficacy with inhalers [190,193] so delivery by nebulizer may soon be standard. There are also several clinical trials comparing JN versus VMN in COPD patients with some publications already pointing to preference for VMN [194].…”
Section: Short-and Long-acting Adrenergic and Muscarinic Agonistsmentioning
confidence: 99%
“…Another clinical trial is assessing the therapeutic potential of an oxyhydrogen generator delivered by nebulizer to COPD patients (NCT02850185). The combination of LAMA with LABA therapies has proven effective in COPD treatment, several studies showed their efficacy with inhalers [190,193] so delivery by nebulizer may soon be standard. There are also several clinical trials comparing JN versus VMN in COPD patients with some publications already pointing to preference for VMN [194].…”
Section: Short-and Long-acting Adrenergic and Muscarinic Agonistsmentioning
confidence: 99%
“… 9 , 10 , 19 FM is a LABA with a rapid onset of action and a sustained dose-dependent bronchodilator effect. 11 FP/FM combination therapy via pMDI was reported to be an efficacious treatment option compared with other ICS/LABA combination therapies via DPI even in patients with moderate to severe asthma. 34 , 35 Iwanaga et al also investigated and reported higher drug deposition in the lungs and peripheral airways after FP/FM via pMDI compared with other ICS/LABA combination therapies via DPI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, triple therapy with BGF has been identified effective and convenient among airway diseases as it can result in an improvement in lung function through distinct and complementary mechanisms. 6 BGF might be a good choice as sequential medicine to systemic glucocorticoids in some refractory asthma patients. In present case, BGF help our patient relieve the burden of symptoms as well as daily activities, which greatly enhance the doctors’ confidence of ICS as well as bronchodilators used in COVID-19 complicated with airway disease.…”
Section: Discussionmentioning
confidence: 99%